MORPHOLOGICAL STATE OF HEART, LIVER AND LUNGS AFTER EXPERIMENTAL THERMAL TRAUMA AND APPLICATION OF CRIOLIOFILIZED XENOGRAFT SUBSTRATE - Небесна, З.М.; Єрошенко, Г.А.; Тупол, Л.Д. (World of Medicine and Biology, 2015)
In the experiment on mature white male rats was performed study of morphological state of the heart, lungs, liver after severe thermal trauma and usage of lyophilized xenographt substrate. It was established that deep burns lead to significant changes in all structural components of organs. It was found that application of lyophilized xenographt substrate after early necrectomy of affected skin prevents development of destructive changes in the muscle membrane of the animal heart, lungs and liver, positively effects on the course of regenerative processes and relatively normalizes the structural organization of organs to the end of the experiment.